Correction to: Survival of Xanthomonas campestris pv. campestris associated with soil and cauliflower crop debris under Brazilian conditions (European Journal of Plant Pathology, (2020), 156, 2, (399-411), 10.1007/s10658-019-01888-8) - Júnior, T. A. F. Silva [UNESP]; Silva, J. C. [UNESP]; Gonçalves, R. M. [UNESP]; Soman, J. M. [UNESP]; Passos, J. R.S. [UNESP]; Maringoni, A. C. [UNESP] (Springer Nature, 2020)
Author family name to be read as Silva Júnior.